2021
DOI: 10.26656/fr.2017.5(1).410
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities and simultaneous HPLC-DAD profiling of polyphenolic compounds from Moringa oleifera Lam. Leaves grown in Bangladesh

Abstract: Moringa oleifera Lam. has been used as a traditional medicine for the treatment of several diseases. In this study, the antioxidant activity and simultaneous HPLC profiling of polyphenolic compounds in 80% ethanol and water extracts of M. oleifera tender and mature leaves available in Bangladesh were investigated. The 80% ethanol extract of M. oleifera tender leaves contained high concentration and more amount of 3,4- dihydroxybenzoic acid, (-) epicatechin and rosmarinic acid (201.32±1.94, 213.08±1.96 and 133.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous research has reported the phytochemicals, namely, kaempferol and quercetin in M. oleifera leaf extracts [ 51 ]. Another study reported the ethanolic extract of M. oleifera contained p-Coumaric acid and quercetin [ 52 ]. Chlorogenic acid, catechin, caffeic acid, rutin, quercetin, and kaempferol were identified in the leaves of M. oleifera using HPLC analysis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported the phytochemicals, namely, kaempferol and quercetin in M. oleifera leaf extracts [ 51 ]. Another study reported the ethanolic extract of M. oleifera contained p-Coumaric acid and quercetin [ 52 ]. Chlorogenic acid, catechin, caffeic acid, rutin, quercetin, and kaempferol were identified in the leaves of M. oleifera using HPLC analysis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…X. granatum sample was taken into a 10 mL test tube separately [36]. 7.5 mL of de-ionized water and 0.5 mL Folin-Ciocalteu reagent (without dilution) were added to each tube followed by the addition of 1.0 mL of 35% (w/v) sodium carbonate.…”
Section: Determination Of the Composition Of X Granatum Tanninmentioning
confidence: 99%
“…Then automatic baseline correction and normalization were carried out by the FTIR built-in software. HPLC-DAD analysis was performed for the detection and quantification of polyphenolic compounds in methanol (100%) extracted X. granatum, mimosa tannin (standard), and quebracho tannin (standard) as delineated by Ahmed [36] with some modifications. HPLC instrument (Shimadzu LC-20A, Japan) consisting of the binary solvent delivery pump (LC-20AT), auto-sampler (SIL-20A HT), column oven (CTO-20A), a detector of photodiode array (SPD-M20A) was used and run by the LC solution software for analysis.…”
Section: Characterization Of the Chemical Structure Of X Granatum Tanninmentioning
confidence: 99%
“…where n = number of treatment; i = initial treatment number. Selected phenolic compounds in the extract of C. decandra were detected and quantified using HPLC-diode array detector (DAD) analysis (Ahmed et al 2021).…”
Section: Methodsmentioning
confidence: 99%